PERANCANGAN SISTEM INFORMASI PENGADAAN LANGSUNG BARANG/JASA PADA UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA BERBASIS WEB - Muhamad Nabila Gozali, - (2018)
The direct procurement of good/service which become object of research guided by Perpres Number 16/2018. The purpose if this research is designing information system direct procurement of goods/services in Pembangunan Nasional "Veteran" Jakarta University to be online computerized with some advantages : direct procurement of goods/services process can be more easily and quickly implemented, direct procurement of goods/services status can be monitored generally ( especially work unit/faculty ), and direct procurement of goods/services will be implemented can get many registered vendors. The stages in analyzing the information system is using PIECES and UML such as Use Case Diagram, Activity Diagram, Sqeuence Diagram. While the system development method used waterfall method, then made interface design is the design of the screen, the design of the screen is a system which connect between user where the system is what will be proposed. User will be easier to do the direct procurement of goods/services